Blockchain concepts in business research – a scoping review - Ioana Cîmpan; Emil Lucian Crișan (Management Matters)
Purpose – The purpose of this paper is to provide a condensed perspective of blockchain-related concepts for business researchers and practitioners, amid the growing popularity of the subject. Design/methodology/approach – This paper is a literature review following the Preferred Reporting Items for Systematic reviews and Meta-Analysis Extension for Scoping Reviews methodology. We have revised 42 papers that have detailed concepts such as blockchain, Web 3.0, blockchain types, affordances, and limitations. Findings – The paper creates a comprehensive overview of blockchain-related concepts. It starts by looking at the blockchain's various definitions and explains the technology's novelty. The components and the process of making a transaction in the blockchain are explained from a combined paradigm, including both business and technological concepts. Further on, the paper discusses the existing types of blockchain, together with the affordances provided by the usage of the technology. The last part includes the limitations of blockchain. Originality/value – The present study reveals the existence of three paradigms while studying the subject: business-centric, technological-centric, and combined. While the primary aim of this research is to explain concepts for business researchers and practitioners, it includes technological aspects as well, therefore, aligning with the combined paradigm.